Ecological relationships at a near-natural treeline, Rolwaling Valley, Nepal Himalaya: Implications for the sensitivity to climate change - Schwab, Niels; Janecka, Karolina; Kaczka, Ryszard J.; Böhner, Jürgen; Chaudhary, Ram Prasad; Scholten, Thomas; Schickhoff, Udo (ERDKUNDE, 2020)
At a global scale, heat deficits during the growing season result in growth limitations, which determine the elevation of natural alpine treelines. Thus, the expected response to global warming is a treeline advance to higher elevations. However, empirical studies of diverse mountain ranges have yielded evidence of both advancing alpine treelines as well as rather insignificant responses. Based on an extensive collection of field data, we analysed population structures and regeneration patterns, investigated population density-environment relationships and correlated tree growth with climate in order to assess the sensitivity to climate warming of a near-natural treeline ecotone in east-central Nepal. The presence of an elevational zone dominated by a gnarled growth form of Rhododendron campanulatum physiognomically classifies the treeline as a krummholz treeline. The fraction of juvenile tree individuals reflects prolific regeneration and stand densification. The species-specific variation in adult and juvenile stand density along the treeline ecotone depends not only on temperature but also on soil, topographic, and other microclimatic conditions. Rhododendron campanulatum shows highest competitiveness in the krummholz belt under a constellation of site conditions influenced by this species itself. By contrast, Abies spectabilis (Himalayan Silver Fir) and Betula utilis (Himalayan Birch) have gained predominance under warmer and more nutrient-rich habitat conditions in the closed forest below. The dense krummholz belt effectively controls the potential upslope migration of subalpine forest tree species. Abies spectabilis growth-climate correlations show changing growth limitations in the course of the 20th century, most likely due to intensified climate warming in recent decades, when decreasing moisture availability during the pre-monsoon season has affected Abies spectabilis’ radial growth. It is evident from our results that to date the treeline has responded to climate warming in terms of stand densities, seed-based regeneration and growth patterns of trees, the treeline position, however, is rather stable. A treeline shift is to be expected in the mid- to long-term only.